A Forgotten Legacy: The Romanov Patronage of Finland's Early Art Collections. Issue 3 (2nd April 2016) - Sopo, Elina
Abstract: The earliest art collections of Finland's National Gallery came into being when, as the Grand Duchy of Finland, it was an autonomous part of imperial Russia (1809–1917). The prevailing view of Finnish museum studies, however, sees the Finnish Art Society, the precursor of the Finnish National Gallery, as being modelled on exclusively European cultural institutions. The history of the Society and its collections have thus been seen as resistant to any alien eastern influences, and as an attempt to differentiate Finnish culture from Russian art collecting practices. Drawing on the theoretical shift in cultural studies from the conception of stable, clearly demarcated cultural identities of nation states toward less rigidly defined identities, the aim of this essay is to reconstruct the hidden Russian presence in Finnish museum historiography. Based on original unpublished sources, my study shows that the earliest support of Finland's cultural infrastructure was given by the Romanov patrons Nicholas I, Alexander II, and Alexander III. By exposing the absence and physical erasure of "imperial identity" in the official Finnish museum narrative, I reveal how museums can at once elevate particular discourses and practices while marginalizing other historical processes in a nation's cultural past.